GAMBARAN KOMBINASI POSISI SEMI FOWLER DAN PURSED LIP BREATHING PADA BP. S DENGAN DIAGNOSA DYSPNEA DI INSTALASI GAWAT DARURAT RS SWASTA DI SEMARANG: CASE REPORT - Hetyningsih, Danik Pri; Pujiastuti, Diah; Sudarto, Silvia (Forind Press, 2025)
Dyspnea or shortness of breath is a feeling of difficulty breathing characterized by shortness of breath and the use of respiratory muscles. Respiratory disorders are the highest contributor to morbidity and mortality in the world. Medical management of dyspnea patients in the emergency room is very important. Pharmacological therapy on the problem of ineffective breathing patterns by providing oxygenation and bronchodilator therapy, while non-pharmacological therapy is a combination of semi-fowler position and PLB. The method in this study uses a case report by intervening with a combination of semi-fowler and PLB positions for 10-15 minutes given 3-4 times. The semi fowler position is a half-sitting position while PLB is a deep breathing technique by drawing air through the nose and releasing air by way of the lips aiming to provide comfort and reduce shortness of breath. The result is a change in dyspnea patients before and after the intervention, before the intervention borg shortness of breath score 4, RR 28-30 x/min, SpO2 92% and after the intervention 3 times the results obtained borg score 0, RR 18 times/min, SpO2 99%. Giving a combination of semi fowler position and pursed lips breathing can improve oxygenation in dyspnoea patients.